2022
DOI: 10.33225/jbse/22.21.325
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Modelling and Analogy on High School Students’ Content Understanding and Transferability: The Case of Atomic Structure

Abstract: Analogies and modelling have been developed and applied in learning and teaching science to facilitate students’ understanding of abstract concepts, such as atomic structure. Considering few studies focus on comparing the effects of two teaching strategies—analogy-based teaching (ABT) and modelling-based teaching (MBT)—this study aims to compare the effects of ABT and MBT on high school students’ content understanding and transferability of atomic concepts in science. Implementing a quasi-experimental design w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 67 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Approaching chemistry learning using analogy has the advantage that it stimulates learning and is significant for students who become more motivated to be involved actively in the learning process. Likewise, other research results proved that implementing an analogous approach to chemistry learning can improve the outcomes (Sutrisno et al, 2020;Xue et al, 2022). In addition, ethnochemistry-based learning makes students more interested in learning chemical concepts since it used to be less exciting and dominated by abstract concepts.…”
Section: Discussionmentioning
confidence: 90%
“…Approaching chemistry learning using analogy has the advantage that it stimulates learning and is significant for students who become more motivated to be involved actively in the learning process. Likewise, other research results proved that implementing an analogous approach to chemistry learning can improve the outcomes (Sutrisno et al, 2020;Xue et al, 2022). In addition, ethnochemistry-based learning makes students more interested in learning chemical concepts since it used to be less exciting and dominated by abstract concepts.…”
Section: Discussionmentioning
confidence: 90%
“…The modeling process supports students in acquiring cognitive domains since during the modeling process, students use analyzing, relational reasoning, synthesizing, testing and debugging (Louca & Zacharia, 2012). Previous studies also showed a positive impact of the modeling process on conceptual understanding and other cognitive domains (Campbell et al, 2015;Dukerich, 2015;Taqwa & Taurusi, 2021;Xue, Sun, Zhu, Huang, & Topping, 2022). Collaborative modeling-based learning is a form of constructivist learner-centered instructional method.…”
Section: Scientific Process Skillsmentioning
confidence: 99%
“…Successful teaching involves versatility, innovation and responsibility to provide an education atmosphere that can meet the basic needs of the learner, it is in line with the aims of education beside to educate is improving human resources [7], [14]. It is applicable to all lessons include physics, which aim to create students' scientific behavior, reasoning ability, concept and analysis mastering also developing science and technology [15], [16]. Students may not interest in the learning if it is not fun so physics learning should be fun.…”
Section: Introductionmentioning
confidence: 99%